Nano-Zirconia as a Protective and Consolidant Material for Marble in Architectural Surfaces - Matea Urbanek; Teba Gil-Díaz; Johannes Lützenkirchen; Valter Castelvetro (Buildings)
Natural weathering of carbonate building surfaces exposed to outdoor conditions can be effectively tackled by appropriate products. The aim of this experimental study was to evaluate the effectiveness of nano-zirconia (n-ZrO2) as a consolidant for calcite surfaces. Sorption kinetics were investigated in batch experiments by applying aqueous dispersions of n-ZrO2 onto model, crushed Apuan marble samples of different bead sizes. Adsorption and desorption by the action of simulated rainwater as an environmentally relevant leaching solution were investigated. Adsorption studies revealed a good chemical affinity between n-ZrO2 and calcite, while desorption resulted in <6% release of n-ZrO2 and 100-fold lower solubility for 1 mm-sized beads compared to controls. These results suggest that n-ZrO2 may adsorb efficiently to calcite and protect the surface from dissolution. The results of further tests performed on artificially aged and consolidated samples of Apuan marble indicate that the application of n-ZrO2 only moderately affects water vapor permeability, water absorption coefficient, and drying behaviour. Therefore, no harmful effects are expected from the treatment. Micromechanical tests showed slightly increased mechanical strength after treatment. The obtained results highlight the effectiveness of n-ZrO2 as a surface consolidant and protective agent for calcite.